2014
DOI: 10.12775/ecoq-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal status of forest trees grown in urban and rural environments in Poland

Abstract: Mycorrhizal status of mature forest trees (horse chestnut, Aesculus hippocastanum L.; white poplar, Populus alba L.; black poplar, P. nigra L.) was investigated in urban habitats under different intensity of anthropogenic pressures (restricted root zone, soil compaction, low air and soil humidity), compared to trees grown in rural environments that were used as reference biological material. Horse chestnut roots were colonized by arbuscular mycorrhizal (AM) fungi, and the two poplar species (white poplar and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Most studies support our finding that plants growing in urban areas have lower AM colonization than plants in rural populations (see Egerton‐Warburton & Allen 2000; Wiseman & Wells 2005; Tyburska et al . 2013). Only one study found similar colonization rates between urban and rural environments in AM (Karliński et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies support our finding that plants growing in urban areas have lower AM colonization than plants in rural populations (see Egerton‐Warburton & Allen 2000; Wiseman & Wells 2005; Tyburska et al . 2013). Only one study found similar colonization rates between urban and rural environments in AM (Karliński et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while previous studies have found that plants in urban soils interact less with AM fungi (Tyburska et al . 2013), and that urban soils have lower spore richness, diversity, and density, than rural soils (Cousins et al . 2003), few studies have explored urban soil properties that affect the AM association (Egerton‐Warburton & Allen 2000; Wiseman & Wells 2005; Buil et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Timonen and Kauppinen [ 22 ] reported that Tilia cordata trees growing in a nursery had different sets of ectomycorrhizal symbionts than trees grown along streets with traffic. However, the relationship between specific environmental conditions and the mycorrhizal status of trees is still not well known [ 23 ]. Taking into account the positive impact of the mycorrhizal relationship for trees performance we investigated the differences of ECM community of trees growing in the park (the favorable habitat conditions) and the trees growing along the streets.…”
Section: Introductionmentioning
confidence: 99%
“…Saline soils contain various dissolved salts, such as NaCl, Na 2 SO 4 , MgSO 4 , CaSO 4 , MgCl 2 , KCl, however the most common type of salt that accumulates in the soil however lower colonization of tree roots by ECM and AM fungi has been found in strongly disturbed urban habitats (i.e. Nielsen and Rasmussen 1999;Bainard et al 2011;Tyburska et al 2013). The symbiotic activity of native mycorrhizal fungi in disturbed urban sites can be supported by basic tillage practices, such as enrichment of the soil with organic matter.…”
Section: Introductionmentioning
confidence: 99%